Physiotherapists’ use and perceptions of digital remote physiotherapy during COVID-19 lockdown in Switzerland: an online cross-sectional survey - Anne-Kathrin Rausch; Heiner Baur; Leah Reicherzer; Markus Wirz; Fabienne Keller; Emmanuelle Opsommer; Veronika Schoeb; Stefano Vercelli; Marco Barbero (Archives of Physiotherapy, 2021)
Abstract Background The Swiss containment strategy for the COVID-19 pandemic during the first wave in spring 2020 resulted in a moratorium on non-urgent physiotherapy via regular direct patient contact. Consequently, such physiotherapy sessions declined by 84%. This study investigates the impact of this moratorium on the use of digital remote physiotherapy in Switzerland during this period and the perceptions of its use by Swiss physiotherapists (PTs). Methods A cross-sectional online questionnaire was distributed between June and August of 2020 via the Swiss Physiotherapy Association (physioswiss) and various associations of physiotherapy specialists (e.g., sport, pediatric) working in both inpatient and outpatient settings. The questionnaire was designed to capture the demographics of participants and the perceptions of PTs using 33 questions in the following domains: Demography; Attitudes towards digital technology; Private and professional use of digital technology; Use of digital technology during therapy; and, Support requirements. Closed and open-ended questions were included and the frequency of answers was analyzed. Non-parametric inferential statistics were used to identify differences, where appropriate. The Checklist for Reporting Results of Internet E-Surveys (CHERRIES) was adopted. Results Participants in the survey were 742 PTs (23.5% male, mean age of 43 years, mean working experience of 18 years) from the German-speaking (75.5%), French-speaking (15.1%), and Italian-speaking (9.4%) regions of Switzerland. The percentage of PTs using digital remote therapy increased from 4.9% prior to the lockdown to 44.6% during the lockdown period. The majority of PTs did not consider that digital remote therapy could complement usual physiotherapy practice and did not plan to continue with digital remote therapy after the pandemic. Conclusions During the lockdown, Swiss PTs adopted various low-cost and easily accessible digital technologies. However, several barriers hampered further implementation of this modality. Specific education and training programs need to be provided among PTs, appropriate digital technologies should be introduced, and a correct reimbursement scheme should be developed. Trial registration COVIDPhysio Registry of World Physiotherapy, registered 15th June 2020 ( https://world.physio/covid-19-information-hub/covid-19-covidphysio-registry ).